Foraging extends beyond food: Hoarding of mental energy and information seeking in response to uncertainty. (2019) - Alquist, Jessica L.; Baumeister, Roy F.
Abstract: When an environment is uncertain, humans and other animals benefit from preparing for and attempting to predict potential outcomes. People respond to uncertainty both by conserving mental energy on tasks unrelated to the source of the uncertainty and by increasing their attentiveness to information related to the uncertainty. This mental hoarding and foraging allow people to prepare in uncertain situations.